Where the wild things aren’t: exploring the utility of rapid, small-scale translocations to improve site selection for shellfish restoration - Alder, Al; Hillman, Jenny R. (Frontiers in Marine Science, 2024)
The assessment of site suitability is a crucial step for informing future successful species reintroductions. It ensures that translocated species have the highest chance of survival in their new environment while minimising ecological risks. However, it can be challenging when risk factors are unknown, especially when working with sessile species that cannot easily relocate to more favourable conditions. Under these scenarios, rapid (1-2 week-long), small-scale (< 1 m2) experimental translocations can help reduce uncertainty and improve restoration outcomes. This study conducted small-scale experimental translocations of green-lipped mussels, Perna canaliculus, to 11 shallow coastal sites spread across Tīkapa Moana/the Hauraki Gulf, Aotearoa/New Zealand to investigate the relationship between predator abundance, environmental factors, and mussel loss to help refine existing site selection criteria. The total number of known mussel predators counted from timelapse images was used as a proxy for potential predator pressure. Translocated mussel survival ranged from 10 - 99% and was best predicted by current speed, wind direction, predator abundance, water clarity, and depth (adjusted R2 = 0.505). Predator abundance was best explained by site location (p = 0.001) and had weak correlations among environmental parameters (Rho = 0.067). These results suggest that small, short-term (1-2 week) experimental translocations can help to refine site selection criteria and reduce uncertainty in the site-selection process for larger-scale shellfish reintroduction efforts with unknown and/or hard-to-control risk factors.